Oxytocin enhances oligodendrocyte development and improves social deficits in autistic rats - Wen, Min; Zheng, Shuang; Luo, Hongbo; Zhang, Yi; Zhou, Bo (Frontiers in Neuroscience, 2025)
PurposeAutism spectrum disorder (ASD) is a neurodevelopmental condition with complex etiological factors, including genetic predisposition and environmental influences. In particular, exposure to environmental stressors in utero has increasingly been implicated in disrupting fetal neurodevelopment and potentially contributing to the pathogenesis of ASD in offspring. The aim of this study was to investigate the therapeutic potential of oxytocin and to elucidate its underlying molecular mechanisms in a valproic acid (VPA) exposure-induced rat model of ASD.MethodsTo generate the ASD offspring model, pregnant rats received intraperitoneal injections of VPA on embryonic day 12.5 (E12.5). A control group was administered saline instead. Only male offspring were included in subsequent experiments. On postnatal day 21 (P21), VPA-exposed offspring were randomly divided into: (1) VPA group (ASD model) and (2) VPA+OT (oxytocin inhaled daily, 400 ug/kg, P21-42) group. Behavioral assessments (social behaviors, stereotyped behaviors, anxiety-like behaviors) and amygdala RNA sequencing were compared across control group, VPA group, and VPA+OT group. Both threshold and threshold-free bioinformatics analysis methods were employed to identify the potential therapeutic mechanisms of oxytocin. The findings were further validated using transmission electron microscopy and qPCR.ResultsIntranasal oxytocin administration significantly ameliorated social deficits, repetitive behaviors, and anxiety-like responses in ASD model rats. Transcriptomic profiling revealed substantial neurodevelopmental abnormalities in VPA group. Consistent results from GSEA enrichment analysis, dynamic gene expression pattern analysis and WGCNA showed significant suppression of oligodendrocyte development and differentiation in the VPA group. Pathway analysis indicated that this functional inhibition was associated with the PI3K/AKT signaling pathway. Oxytocin may promote oligodendrocyte development and differentiation by activating the PI3K/AKT pathway, thereby ameliorating social deficits. Further validation by transmission electron microscopy and qPCR confirmed that oxytocin treatment improved myelination deficits in the ASD rat model.ConclusionsOur findings demonstrate that oxytocin significantly improve social interaction deficits in the VPA-induced autism model, which may be related to its activation of the PI3K/AKT pathway to promote oligodendrocyte development and differentiation.